Heart transplantation and antibody-mediated rejection: role of myocardial strain as an early marker of cardiac dysfunction in patients with anti-HLA antibody. (14th October 2021) - Sciaccaluga, C; Natali, B.M; Mandoli, G.E; Sisti, N; Righini, F.M; Menci, D; D'Errico, A; Benfari, G; D'Ascenzi, F; Cavigli, L; Focardi, M; Valente, S; et al.
Abstract: Background: Antibody-mediated rejection of the transplanted heart is still currently diagnosed by endomyocardial biopsy whereas clinical elements, anti-Human Leukocite Antigens (HLA) antibody and graft dysfunction represents supplementary components. Purpose: The aim of the study was to identify though a non-invasive imaging technique, such as advanced transthoracic echocardiography, early signs of altered cardiac function in patients with anti-HLA antibodies and no histological signs of antibody-mediated rejection. Methods: The study population included 117 heart transplanted patients, in whom both acute and chronic rejection was excluded. They were divided into two groups "HLA+`' (45 patients) and "HLA−" (72 patients), based on the presence and the absence of circulating anti-HLA antibodies, respectively. The echocardiographic exam was performed within one week from the biopsy, including Speckle Tracking analysis. Results: Deceleration Time of E wave was the strongest traditional echocardiographic parameter which correlated with circulating anti-HLA antibodies (165±39, 5 vs 196, 5±25; p<0.001). Regarding strain analysis, both left ventricular global longitudinal strain (−16, 1±3, 4 vs −19, 8±2, 0; p<0.001) and right ventricular strain (−17, 2±0, 7 vs −20, 6±0, 5; p=0.0002) differed significantly between the two subgroups (Figure 1). On the other hand, neither peak atrial longitudinal strain nor peak atrial contraction strain showed a significant correlation with anti-HLA antibodies. Conclusion: The presence of circulating anti-HLA antibodies seems to be correlated with a mild cardiac dysfunction, even in the absence of antibody-mediated rejection. This subtle dysfunction is not completely detectable by standard echocardiographic parameters, whereas strain analysis has showed promising results since it revealed more clearly an impaired function of both ventricles in heart transplanted HLA+ patients, with potentially important clinical repercussion. FUNDunding Acknowledgement: Type of funding sources: None.